Assessment of psychological profile of national and international level judo players of India - Rathore, A.; Pathak, M.; Wani, Z. A.; Haroon, M.; Perray, P.; Bhat, R. A. (International Journal of Innovative Research in Science, Engineering and Technology, 2020)
In this modern era of competitions the psychological preparation and physiological fitness of a sportsman isas much important as teaching of different skills of a game on the scientific lines. The craze for winning medals in the Olympics and other international competitions has catalysed the sport scientists to take "interest in exploring all the aspects and possibilities which can contribute to enhance sports performance to undreamt heights. Psychological make-up here, to a great extent, encompasses personality structure, motivation and emotional control. Athlete development systems and programmers are no longer adequate if they only emphasize skill and physical development. The inclusion of sound psychological principles and practices in training and competition preparations and conduct is a necessary ingredient of modern sport.